CALOSOTOMY IN PHARMACORESISTANT EPILEPSY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Epilepsy is a polyetiological, common disease of the nervous system, which is diagnosed in 1–2% of the adult population and 3–4% of children. Most patients are successfully treated with antiepileptic drugs (AEDs), but long-term, sometimes lifelong, use of AEDs causes side effects, even with complete control of epileptic seizures. At the same time, almost 20-25% of epilepsy patients are resistant to anticonvulsant therapy, and surgical treatment is indicated for them [1].